Improving timeliness and completion of infant vaccination among infants in Nigerian urban slums through older women's participation (2022)
Nigerian urban slums have a high population of infants with suboptimal vaccination despite previous interventions. Older women traditionally play supervisory roles in infant care in Nigeria but their influence is untapped in infant vaccination. This study sought to determine if training of older women (_35 years) in urban slum communities in Ibadan, South west Nigeria, and involving them in infant vaccination will improve infant vaccination timeliness and completion. This was a randomized experimental community study and pregnant women in their third trimester, residing in seven urban slum communities were randomized using their antenatal clinics (ANCs) into intervention (six ANCs) and control groups (six ANCs). The older women who will supervise the care of the infants of pregnant women in the intervention group had seven sessions of training on the importance of infant vaccination timeliness and completion. The vaccinations of the infants from both groups were compared from birth till 9 months. Data were analyzed using descriptive statistics and Chi square test at a = 0.05. There were 96 older women, 198 pregnant women (105 in intervention group and 93 controls) and 202 infants (109 in intervention group and 93 controls). Infants in the intervention group (67.9%) significantly had both timely and complete vaccinations compared with those in the control group (36.6%). Vaccines given at birth were the least timely in both groups. More infants whose older women caregiver were married had timely and complete vaccinations. Also, a higher proportion of male infants, low birth weight babies and infants with older women caregiver with at most two children had timely and completed vaccinations but these were not statistically significant. Training of older women caregivers improved infant vaccination timeliness and completion in these urban slum communities. This model may improve infant vaccination in other similar urban slum settings.